Changes in the Levels of Some Biochemical Parameters in the Serum of Children in Response to the Giardiasis Infection - Mageed, Sarmad N. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2019)
Giardiasis is one of the most common intestinal protozoan infections worldwide. The study aimed to determine the levels of a number of biochemical parameters in the sera of children with giardiasis without receiving any medication for the treatment of giardiasis or intestinal helminthic infections in the previous 7 days. The study conducted 34 (19 females and 15 males) children and 34 (18 females and 16 males) healthy children as a control group. The mean ages of infected children and control groups were 8 ± 2 and 7 ± 2 years, respectively. Serum levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), creatinine, urea, sodium, potassium, uric acid, and albumin were determined. AST level in males was significantly higher than healthy children control (14.20 ± 1.896 and 10.06 ± 0.699), respectively (P < 0.05), and no significant difference in females was noticed whereas the significant increases in ALT level were found when compared to control (12.43 ± 0.806 and 8.666 ± 0.449), for female, respectively, whereas no significant change in males was observed. Creatinine levels showed significant decrease in females when compared to control (57.72 ± 1.170 and 73.37 ± 1.635) (P ≤ 0.001), respectively.